Astronomy and Local Culture Dialectics; Kiai á¹¢Äliá¸¥ Darat's Idea in the Integration of the Hijriyah Calender - Mawahib, Muhamad Zainal; Rosyid, Maskur; Hidayat, Muhammad Syarif (Faculty of Shariah and Law, State Islamic University (UIN) Walisongo, 2019)
This paper aims to trace the genealogy of the Kiai á¹¢Äliá¸¥ Darat in the field of falak sciences and the approach he used in uniting the differences in the initial determination of Ramadan in Semarang. This study is important, considering Kiai á¹¢Äliá¸¥ Darat is more an expert in the field of Sufism. On the other hand, Kiai á¹¢Äliá¸¥ Darat was also positioned as an early generation Falak Indonesian expert (salaf). This paper includes a historical study that conducts critical analysis of data that has been isolated from various literatures. The results of the study showed that the expertise of Kiai á¹¢Äliá¸¥ Darat in the field of falak knowledge was obtained when conducting scientific jouney for Semarang scholars to al-Haramayn scholars. Kiai á¹¢Äliá¸¥ Darat initiated a deliberation to determine the beginning of the month of Ramadan. This discussion involved ulama, astronomer, habaib and umara in Kauman Mosque in Semarang. The idea of deliberation is aimed at eliminating differences in society in determining the beginning of fasting. The idea of the initial unification of Ramadlan through deliberation was the substance of the Dugderan Tradition in Semarang, Central Java